Human papillomavirus infection and risk of cardiovascular disease: A population-based matched cohort study with sibling analysis - Yunyang Deng; Mark Clements; Chaonan Shen; Jonas F. Ludvigsson; Qing Shen; Jiayao Lei (PLOS Medicine, 2026)
Background The role of human papillomavirus (HPV) in cardiovascular disease (CVD) remains unclear. We aimed to investigate the associations of HPV infection with incident CVD and CVD-related mortality. Methods and findings In this population-based matched cohort study based on Swedish national registers, we identified women with an incident HPV infection during 2006 and 2024 ( N = 497,445), and age-matched each woman with five women without infection. The time-varying associations between HPV infection and CVD were assessed using flexible parametric models, which also provided hazard ratios (HRs) and 95% confidence intervals (CIs) after adjusting for sociodemographic factors, HPV vaccination, chronic diseases, and parental history of related diseases. To control for familial factors, we also compared 143,787 women with HPV infection to their 174,637 unaffected full siblings. A total of 28,793 and 128,373 incident CVDs were identified in women with and without HPV infection (Incidence: 8.27 and 7.93 per 1,000 person-years), respectively. Additionally, 1,221 and 4,941 CVD-related deaths were observed among women with and without HPV infection (Mortality: 33.73 and 29.39 per 100,000 person-years), respectively. The risks of incident CVD and mortality were most pronounced within the first follow-up year and attenuated thereafter. Overall, women with HPV infection had an increased risk of incident CVD (adjusted HR 1.07, 95% CI [1.05, 1.08], absolute rate difference 0.53 per 1,000 person-years, population-attributable fraction 1.16%) and CVD-related mortality (adjusted HR 1.25, 95% CI [1.16, 1.34], absolute rate difference 6.71 per 100,000 person-years, population-attributable fraction 4.12%) than those without. During the first follow-up year, the adjusted HRs for incident CVD and CVD-related mortality were 1.43 (95% CI [1.38, 1.48]) and 1.86 (95% CI [1.41, 2.45]), respectively. Beyond the first follow-up year, the corresponding adjusted HRs decreased to 1.02 (95% CI [1.01, 1.04]) for incident CVD and 1.21 (95% CI [1.12, 1.30]) for CVD-related mortality. In sibling comparisons, positive associations with both outcomes were also observed. Women with HPV infection had fully adjusted HRs of 1.05 (95% CI [1.01, 1.08]) for incident CVD and 1.25 (95% CI [1.01, 1.53]) for CVD-related mortality compared to their siblings without HPV infections. The main limitations of this study are its observational design, which precludes causal inference between HPV infection and CVD, and the potential misclassification of HPV infection, which may have biased the association towards the null. Conclusions HPV infection was associated with increased risk of incident CVD and CVD-related mortality. The findings suggested that clinicians should be aware of a slightly elevated CVD risk in women with HPV, especially during the first year following an infection. However, given the small absolute difference, women should not be unduly concerned.